APPLICATION OF THE COOPERATIVE LEARNING MODEL TYPE STUDENT FACILITATOR AND EXPLAINING TO THE UNDERSTANDING OF STUDENTS' MATHEMATICAL CONCEPTS - Fepryna Yenti; Melia Roza; Sefrinal . (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2023)
Understanding mathematical concepts is one of the objectives of learning mathematics so that this ability is expected to develop and improve. However, it was obtained that the understanding of mathematical concepts of grade X MIPA students was still low. The Student Facilitator And Explaining teaching model is expected to facilitate students in increasing their understanding of mathematical concepts. The purpose of this study was to find out whether the understanding of mathematical concepts of students who learn with the Student Facilitator And Explaining learning model is better than the understanding of mathematical concepts of students who learn using conventional learning. The experimental research design used was Randomized Control Group Only Design. Sampling is done by Simple Random Sampling technique. The test conducted in this study is the t test, with the final conclusion obtained that the understanding of students' mathematical concepts using the Student Facilitator And Explaining Cooperative Learning Model is better than students' understanding of mathematical concepts using Conventional Learning.